Migrants’ Population, Residential Segregation, and Metropolitan Spaces - Insights from the Italian Experience over the Last 20 Years - Benassi, Federico; Crisci, Massimiliano; Matthews, Stephen A.; Rimoldi, Stefania Maria Lorenza (Migration Letters, 2022)
Southern European studies of migrants’ spatial distribution within metropolitan cities (MCs) are increasingly relevant to understanding residential segregation and marginalisation, particularly of foreign nationals. This paper leverages original and partially unpublished data to examine overall and foreign national specific segregation over two decades in Rome MC and Milan MC, the two largest Italian MCs. We introduce a 5-class concentric ring typology to describe and uncover geographical patterns within the MCs and focus on the spatial and temporal distribution of four selected foreign nationalities: Romanian, Bangladeshi, Chinese, and Filipino. Results reveal heterogeneity in overall and foreign national specific distributions over time both within and between Rome MC and Milan MC. Comparing across groups and MCs we identify similarities but also unique patterns. These results shed light on the peculiarity of the urban demographic Italian landscape and raise questions regarding recent theories about residential segregation in the urban contexts of Southern Europe.